Phân lập 3 hợp chất lignan từ lá cây đề (Ficus religiosa L.) - Hương, Hoàng Thanh; Quang, Trần Hồng; Ính, Cầm Thị; Minh, Châu Văn; Kiệm, Phan Văn; Quetin-Leclercq, Joelie; Vander Heyden, Yvan (Vietnam Journal of Chemistry, 2014)
Phytochemical study on the leaves of Ficus religiosa led to the isolation of three lignans. Their chemical structures were determined to be (+)-pinoresinol (1), pinoresinol di-O-b-D-glucopyranoside (2) and syringaresinol O-b-D-glucopyranoside (3) by means of spectroscopic studies including NMR and ESI mass spectra. The antioxidant activities of these compounds were screened using DPPH system. Among them, compounds 1 and 3 exhibited significant scavenging activities with EC50 values of 16.90 and 16.93 mM, respectively.